MEWUJUDKAN LINGKUNGAN BERSIH MELALUI KOLABORASI PENGABDIAN MASYARAKAT DI DESA MEKARSARI: Creating A Clean Environment Through Community Service Collaboration In Mekarsari Village - Aminullah, Aminullah; Subrata, I Gusti Made; Jaya, Nenet Natasudian; Marini, Ida Ayu Ketut; Solihun, Siti; Zulaifi, Reza; Zainuddin, M.; Sativa, Denianto Yoga; Sardi, Idris; Zainab, Siti (Al-Amal: Jurnal Pengabdian Masyarakat, 2024)
community service in Mekarsari Village. Methods for implementing service include: forming a service team, preparing service needs, cleaning the environment and providing rubbish bins. Service activities carried out include: 1) Formation of a service team consisting of academics, the community and village government. 2) Preparation for the needs for implementing the service begins with directing and checking tools and materials in the form of brooms, shovels, buckets, plastic, hoes and sickles prepared by the community. 3) Environmental clean-up is carried out around the Malaka hamlet kindergarten to maintain the comfort and health, especially of children, as well as to create interest and life for tourists because it is on the tourist route, and 4) procurement of rubbish bins, procurement of rubbish bins purchased from local community wickerwork and then painted as markers and fixed to make them look different or better